Characterization of Oil Well Cement–Formation Sheath Bond Strength - Musaed N. J. AlAwad; Khalid A. Fattah (Eng, 2025)
The aim of this study is to develop a simple and reliable laboratory testing procedure for evaluating the bond strength of cement–formation sheaths that considers cement slurry composition and contamination as well as formation strength and formation surface conditions (roughness and contamination). Additionally, a simple and practical empirical correlation is developed for predicting cement–rock bond strength based on the routine mechanical properties of hard-set cement and formation rock. Cement slurries composed of Yamama cement type 1 and 25% local Saudi sand, in addition to 40% fresh water, are used for all investigations in this study. Oil well cementing is a crucial and essential operation in the drilling and completion of oil and gas wells. Cement is used to protect casing strings, isolate zones for production purposes, and address various hole problems. To effectively perform the cementing process, the cement slurry must be carefully engineered to meet the specific requirements of the reservoir conditions. In oil well cementing, the cement sheath is a crucial component of the wellbore system, responsible for maintaining structural integrity and preventing leakage. Shear bond strength refers to the force required to initiate the movement of cement from the rock formation or movement of the steel casing pipe from the cement sheath. Cement–formation sheath bond strength is a critical issue in the field of petroleum engineering and well cementing. Cement plays a crucial role in sealing the annulus (the space between the casing and the formation) and ensuring the structural integrity of the well. The bond strength between the cement and the surrounding geological formation is key to preventing issues such as fluid migration, gas leaks, and wellbore instability. To achieve the study objectives, sandstone and sandstone–cement composite samples are tested using conventional standard mechanical tests, and the results are used to predict cement–formation sheath bond strength. The utilized tests include uniaxial compression, direct tensile, and indirect tensile (Brazilian) tests. The predicted cement–rock sheath bond strength is compared to the conventional laboratory direct cement–formation sheath strength test outcomes. The results obtained from this study show that the modified uniaxial compression test, when used to evaluate cement–formation shear bond strength using cement–rock composite samples, provides reliable predictions for cement–formation sheath bond strength with an average error of less than 5%. Therefore, modified uniaxial compression testing using cement–rock composite samples can be standardized as a practical laboratory method for evaluating cement–formation sheath bond strength. Alternatively, for a simpler and more reliable prediction of cement–formation sheath bond strength (with an average error of less than 5%), the empirical correlation developed in this study using the standard compressive strength value of hard-set cement and the standard compressive strength value of the formation rock can be employed separately. For the standardization of this methodology, more generalized research should be conducted using other types of oil well cement and formation rocks.